Cyanotic tetralogy of Fallot in a 77 year old man. Issue 739 (May 1987) - Thomas, S. H.; Bass, P.; Pambakian, H.; Marigold, J. H.
Abstract : We report the clinical details of a 77 year old man with classical tetralogy of Fallot. The patient had clubbing and cyanosis at birth, and exertional squatting in childhood. He was asymptomatic as an adult until the seventh decade, when he developed biventricular failure and had an episode of bacterial endocarditis. He finally died of cerebral infarction and bronchopneumonia following abdominal surgery. In spite of investigations, the diagnosis was not made in life, but only discovered at post-mortem. A persistent ductus arteriosus was also found. Increased pulmonary blood flow via the ductus is believed to have facilitated this patient's unusual longevity.